ARTHROPODA COLLECTION ALBUM: A VALID, PRACTICAL, AND EFFECTIVE MEDIA DEVELOPMENT (International Conference on Social and Islamic Studies, 2022)
The population of arthropods, which is abundant on the UIN Alauddin Makassar campus, can be utilized in the learning process, especially for invertebrates. This study was to evaluate the validity, practicality, and effectiveness of arthropod collection albums. The research method used was Research and Development (R&D) with the type of ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The sampling technique was a purposive sampling technique with 12 biology education students. Validity data was obtained through a validation sheet, practicality data through a questionnaire, and effectiveness data through a learning outcome test. The results showed that 1) expert validation was very valid, with a percentage level of 90.8%. 2) The level of practicality was very high, with 95.6% for students' responses and 97% for lecturers' responses. 3) The results of the small group test are categorized as effective with a 100% completeness percentage. In other words, the arthropod collection album created was valid, practical, and effective. Besides the media being simple and easy to use, the results also implied that the product could increase interest and learning outcomes and help educators deliver material that is difficult to present in class.